Early sown Indian mustard varieties — A profitable substitute to toria - Yadav, D K; Dass, B; Giri, S C; Singh, Rajendra; Singh, Naveen; V, Sujata; Prabhu, K V (Indian Farming, 2015)
Toria being a low yielder and less remunerative crop as compared to Indian mustard, some good varieties of Indian mustard have been developed which are maturing between 100 – 120 days. For getting the higher returns from Brassicas, these early sown short duration varieties can be adopted as a substitute to toria.